2001
DOI: 10.1128/iai.69.4.2462-2469.2001
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barré Syndrome- and Miller Fisher Syndrome-Associated Campylobacter jejuni Lipopolysaccharides Induce Anti-GM 1 and Anti-GQ 1b Antibodies in Rabbits

Abstract: Campylobacter jejuni infections are thought to induce antiganglioside antibodies in patients with GuillainBarré syndrome (GBS) and Miller Fisher syndrome (MFS) by molecular mimicry between C. jejuni lipopolysaccharides (LPS) and gangliosides. We used purified LPS fractions from five Campylobacter strains to induce antiganglioside responses in rabbits. The animals that received injections with LPS from GBS-associated strains developed anti-GM 1 and anti-GA 1 antibodies. Animals injected with LPS from one MFS-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
57
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 35 publications
4
57
0
Order By: Relevance
“…Our studies confirm and extend earlier reports with LPS from Campylobacter strains isolated from GBS, MFS, and uncomplicated enteritis patients (1,12,28,35).…”
Section: Discussionsupporting
confidence: 81%
“…Our studies confirm and extend earlier reports with LPS from Campylobacter strains isolated from GBS, MFS, and uncomplicated enteritis patients (1,12,28,35).…”
Section: Discussionsupporting
confidence: 81%
“…Chemical and structural analysis of lipopolysaccharide (LPS) and lipooligosaccharide (LOS) outer core oligosaccharide (core OS) structures from C. jejuni serotypes isolated from GBS and non-GBS patients have identified sialylated moieties with configurations identical to those of several gangliosides (9,11,42,44,45,50). For example, LPSs from C. jejuni HS:19, a serotype commonly associated with GBS, have been shown to contain GM1-, GD1a-, GD3-, and GT1a-like motifs, and antibody mimicry is supported by the finding that immunization of experimental animals with these LPSs produces the corresponding anti-ganglioside antibody response (4,18). Serotyping studies have determined that certain C. jejuni serotypes, including HS:19, have greater potential for triggering GBS, and this may be due to quantitative differences in ganglioside-like LPS and LOS epitopes compared with non-GBS-associated strains (9,44,50).…”
mentioning
confidence: 76%
“…The mimic most often associated with GBS is GM 1 , and the mimic most often associated with the Miller Fisher variant of GBS, which affects the ocular nerves, is GQ 1b (4,9,61). Recently, it was demonstrated that the immunization of rabbits with purified C. jejuni LOS containing a GM 1 mimic resulted in high levels of anti-GM 1 antibodies and symptoms of GBS in the animals (2,64).…”
mentioning
confidence: 99%